Irrigation Capital Requirements and Energy Costs - Dumler, Troy J.; Rogers, Danny H. (My University, 2004)
This publication describes the economic advantages and disadvantages of irrigation in production agriculture.
MF836_2004_10
Keywords: MF836; Economics; MF